Prevalence of hypertension among tribals of Jharkhand with chest discomfort - Khoya, Leo Minkan; Xalxo, Anima Ranjni; Ekka, Alok Praveen (International Journal of Research in Medical Sciences, 2018)
Background: Cross sectional observational comparative study in a tertiary care hospital on Prevalence of Hypertension among tribals of Jharkhand with Chest discomfort. Methods: 102 subjects (53 male and 49 female) were selected for the study, who had presented with chest discomfort and history of Hypertension. Results: In the current study total 102 subjects were taken, 53 were males. Among tribal males prevalence rate of hypertension, using (J.N.C.-7) criteria majority of them (41subjects 77.35%) were Prehypertensive. 8 subjects (15.09%) had normal blood pressure, 3 subjects (5.66%) had stage -I hypertension and only 1 subject (1.88%) had stage-2 hypertension. In females out of 49 subjects 28 subjects (57.14%) were pre hypertensive, 17 subjects (34.69%) were Normotensive and only 2 subjects (4.08 %) had stage -1 hypertension, as well as 2 subjects (4.08 %) had stage-2 hypertension. Conclusions: The prevalence of Hypertension among tribal patients of chest discomfort was found to be prehypertensive in 40.19% and hypertensive in 3.92% among male and among female tribal’s prehypertensive in 27.45% and hypertensive in 3.92%.